Guru Nanak and The Jogis Tradition: A Historical Context (British Journal of Multidisciplinary and Advanced Studies, 2024)
Guru Nanak’s attitude to contemporary religion is informed by ideas and values which induce him not to identify himself with any of the existing forms of established religion.  Infact, he applies those ideas consistently to evaluate all contemporary belief and practice. The closest he comes to an explicit appreciation for any kind of individuals, it is for the sadhs and sants.[i] Guru Nanak came in the line of the great saints, who emphasized only personal experience of the Divine is what the philosopher calls “mystic experience” as the core of true religion. [ii] There are many references to siddhas, yogins (jogis), nathas and avadhutas, not only in the Japu and the Sidh-gosthi but also in many other hymns and devotional songs by Guru Nanak and preserved in Guru Granth Sahib, said to have been complied in 1604A.D.[iii]  Guru Nanak’s encounters with jogis have remained a favourite theme of Sikh literature for nearly four centuries. This tradition was well established in the time of Bhai Gurdas in whose Vars we have one of the earliest interpretations of Guru Nanak’s attitude towards the jogis.[iv] The present paper seeks to highlights the Guru Nanak ideas associated with the siddhas, yogi and nathas of medieval India.